A gestão educacional inclusiva na escola - Pinheiro, Cely Rosa (2015)
Data from the school census indicate that in 2014 more than 698 thousand children with special needs were enrolled in regular teaching classrooms. And for these children to not be only data from a statistical research, but for them to truly participate in the activities of the school and reach gains in their physical, intellectual, affectionate and social development, all who are involved with education need to put effort into this, and there needs to be a qualification of this human capital which is directly involved with this public. Having in view this panorama this research has as its central theme inclusive educational management in regular teaching situations. We had as our general goal to discuss the importance of teachers, coordinators, psychologist, parents and other persons involved in the teaching-learning process within a teaching institution to work with children with special needs with an inclusive and ethical view. As specific goals we propose: a) Comprehend the importance of their role in the process of inclusion of a child with special needs in the school and in society; b) Comprehend the importance of the role of management and of the others involved in the educational process within the institution in the process of teachinglearning; c) Reiterate and strengthen the historic commitment of educators with the quality of the school; d) Emphasize didactics and teaching practices as epistemological and curricular component areas to form a strong base for the teaching and learning processes as a practice of social inclusion and political emancipation. The motivation arose from the reports of graduates of the pedagogy program in the component Special and Inclusive Education where we observed their lack of knowledge and that of the management of the institutions in which they were doing their internships about inclusive education. We believe that the great social relevance of the Project is the awareness raising of the importance of the preparation of the professionals involved with special education and of the community in general making it possible that these may work in a satisfactory and ethical way. To fulfill the goals outlined a bibliographic research was carried out of a descriptive, qualitative approach. We used in our constructions various authors within which I highlight: Boff, Chalita, Hoffmann and Tiba. As results we perceived that the persons involved in our teaching system have the knowledge of the need to include children with special needs in the regular teaching network. We verified that they perceive the need to qualify the professionals which work with these children, however the necessary provisions for this practice to be consolidated are still far from the ideal.